Community Empowerment Strategy to Improve the Welfare of Single Parent Women's Families - Sutati, Ajeng Dwi Gayuh; Ariefianto, Lutfi; Hilmi, Muhammad Irfan (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
The opaque gambir business is one of the businesses in Winongan Lor Village that was started by a single parent. The business was established with the help of an empowerment strategy to expand sources of income and improve family welfare. Through this empowerment strategy in an effort to increase welfare, it can provide insight, foster an attitude of independence, especially for single parent women, and can grow small industries that are empowered and can implement them for economic development in improving family welfare. The purpose of this study was to determine the strategy of empowerment through the gambir opak business in an effort to increase the welfare of single parent women's families in Winongan Lor Village by using a qualitative descriptive research method that is suitable for this phenomenon. In implementing the empowerment strategy, there are three scopes, namely social assistance, institutional strengthening and partnership strengthening. Meanwhile, to determine the level of family welfare, there are indicators of a prosperous family II and an indicator of a prosperous family III